Pharmacological and Phytochemical Activities of Celery Roots and Stems (Apium graveolens L.): Literature Review - Sindi Ari Anggara (International Journal Of Health Science, 2026)
Celery (Apium graveolens L.) is an herbaceous plant of the Apiaceae family used in traditional medicine to lower blood pressure, treat digestive disorders, and maintain liver and kidney health. Comparative studies on phytochemical content and pharmacological activities of each plant part remain limited. This study aimed to review antioxidant, anti-inflammatory, and antihypertensive activities and identify phytochemical compounds in each part based on literature from 2020 to 2025. This study used a literature review design with the PICOS framework and secondary data from Google Scholar, PubMed, ScienceDirect, and ResearchGate, conducted at STIKes Al-Fatah Bengkulu over two months. The findings demonstrated that celery roots and stems possess antioxidant, anti-inflammatory, and antihypertensive activities attributed to flavonoids, phenolic compounds, phthalides, essential oils, coumarins, triterpenoids, and minerals. Antioxidant activity was reflected by free radical scavenging capacity and enhancement of endogenous antioxidant defense systems, while anti-inflammatory activity involved inhibition of pro-inflammatory mediators and inflammation-related enzymes. Antihypertensive effects were associated with inhibition of angiotensin-converting enzyme (ACE), vasodilation, diuretic activity, and improved electrolyte balance. Overall, celery stems exhibited more consistent pharmacological evidence, particularly for antihypertensive activity supported by clinical studies, whereas celery roots showed promising potential that requires further experimental and clinical validation. These findings provide scientific evidence supporting the development of celery as a standardized herbal medicine and phytopharmaceutical raw material.